August : a novel - Wink, Callan (Random House, 2020)
August is an average twelve-year-old. He likes dogs and fishing and doesn<U+2019>t mind early-morning chores on his family<U+2019>s Michigan dairy farm. But following his parents<U+2019> messy divorce, his mother decides that she and August need to start over in a new town. There, he tries to be an average teen<U+2014>playing football and doing homework<U+2014>but when his role in a shocking act of violence throws him off course once more, he flees to a ranch in rural Montana, where he learns that even the smallest communities have dark secrets. Covering August's adolescence, from age twelve to nineteen, this gorgeously written novel bears witness to the joys and traumas that irrevocably shape us all. Filled with unforgettable characters and stunning natural landscapes, this book is a moving and provocative look at growing up in the American heartland.